The postcolonial playground: colonial narratives in contemporary tourism - Smith, Sean P (Department of English Language and Literature, 2017)
This survey of twentieth and twenty-first century novels, guidebooks, magazines, and the social media platform Instagram illustrates the discursive paradigm by which Western backpacking tourists encounter the formerly colonized world. The "postcolonial playground" avails the non-Western world as a theatre for recreation and meaning-making, an engagement which renders locals as accessories to an experience, perpetuating colonial-era power dialectics that continue to privilege the Western subject over the individuals in whose homes they travel. Ideologically and in praxis, the postcolonial playground has become the naturalized disposition of Western tourists seeking their next holiday. In so many words, the formerly colonized world has been recolonized by tourists, who are oblivious to the regime of privilege that extorts locals in popular tourist destinations.